Net positive how courageous companies thrive by giving more than they take - Polman, Paul. (Boston Harvard Business Review Press, 2021)
The ex-Unilever CEO who increased his shareholders' returns by 300% while ensuring the company ranked #1 in the world for sustainability for eleven years running has, for the first time, revealed how to do it. Teaming up with Andrew Winston, one of the world's most authoritative voices on corporate sustainability, Paul Polman shows business leaders how to take on humanity's greatest and most urgent challenges?climate change and inequality?and build a thriving business as a result.
Includes index
Keywords: Business ethics